Uptake and Distribution of Labeled Carbon from (14)C-Asparagine by Mycobacterium tuberculosis - Lyon, Richard H. (1969)
Asparagine supplies not only nitrogen but also carbon to growing cells of Myobacterium tuberculosis. The carbon of asparagine is rapidly taken up and extensively utilized.